Influence of partial k-space filling on the quality of magnetic resonance images - Jornada,Tiago da Silva (2016)
Abstract Objective: To study the influence that the scan percentage tool used in partial k-space acquisition has on the quality of images obtained with magnetic resonance imaging equipment. Materials and Methods: A Philips 1.5 T magnetic resonance imaging scanner was used in order to obtain phantom images for quality control tests and images of the knee of an adult male. Results: There were no significant variations in the uniformity and signal-to-noise ratios with the phantom images. However, analysis of the high-contrast spatial resolution revealed significant degradation when scan percentages of 70% and 85% were used in the acquisition of T1- and T2-weighted images, respectively. There was significant degradation when a scan percentage of 25% was used in T1- and T2-weighted in vivo images (p ≤ 0.01 for both). Conclusion: The use of tools that limit the k-space is not recommended without knowledge of their effect on image quality.